A bipolar plate and a method for preparing the same
By preparing specific raw materials in the bipolar plate and heating and pressing molding, a three-dimensional conductive network is constructed, which solves the problem that bipolar plates are difficult to have high conductivity, corrosion resistance and sealing properties, and achieves excellent conductivity and corrosion resistance.
Patent Information
- Application Number
- CN202110867570.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-07-30
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2041-07-30
AI Technical Summary
It is difficult for existing bipolar plates to have high conductivity, corrosion resistance and sealing properties.
By preparing prefabricated bodies of titanium carbide, graphite, carbon black and composite polymer fillers, and molding under heating and pressurization, a three-dimensional conductive network is constructed to prepare a bipolar plate with excellent conductivity, corrosion resistance and sealing.
It achieves high conductivity of bipolar plates, while taking into account corrosion resistance and sealing, improving the comprehensive performance of bipolar plates.
Smart Images

Figure CN113594487B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a conductive composite material, and in particular to a bipolar plate and a preparation method thereof. Background Art
[0002] Proton exchange membrane fuel cells (PEMFCs) are considered to be a potential new energy generation device due to their high energy density, good response to various loads, low temperature operation, and fast start-up capabilities. PEMFC is the most common fuel cell and the main force in fuel cell applications. Bipolar plates are one of the most intensively studied components in fuel cells. Bipolar plates have important functions in battery stacks: uniformly distribute fuel gas and oxygen, collect and conduct current from the anode to the cathode of the next connected single cell, thereby integrating into a fuel cell stack that meets voltage requirements, and support the membrane electrode assembly (MEA) through proper internal water management, heat dissipation, and by maintaining clamping pressure. The development of fuel cell bipolar plates is becoming the key to research in the fuel cell industry.
[0003] At present, bipolar plates are divided into metal bipolar plates, graphite bipolar plates and composite bipolar plates according to the different preparation materials. Metal plates are stamped to form bipolar plates with flow channels, which are called metal bipolar plates. They obtain protective coatings through surface modification, but under long-term harsh working conditions, the coatings will be corroded and lose their protective function. Graphite bipolar plates are bipolar plates in which high-density graphite is graphitized under high temperature and high pressure and mechanically processed to form gas flow channels. They have a long life, but graphite is brittle, and the processing technology is demanding, and the preparation is difficult and costly. Composite bipolar plates are formed by injection or molding one-time after forming prepregs by mixing resin with graphite powder and reinforcing materials. They have good comprehensive performance, good electrical conductivity, corrosion resistance, and mechanical properties such as bending and compression resistance. In the preparation of composite bipolar plates, compression molding is more widely used than injection molding. It mainly uses hydraulic presses and molds to heat and pressurize the mixture of conductive fillers and resins that are evenly mixed, accelerate resin curing and material shaping, and demold to obtain bipolar plates with specified shapes and flow channels. The molding process requires simple equipment and low requirements for material fluidity. The prepared bipolar plates have high density, precise size, small shrinkage and good performance. In addition, the flow channel is directly formed during the molding process, without the need for mechanical processing procedures, and can be mass-produced with a short production cycle and high production efficiency. Carbon-based composite bipolar plates are a type of composite bipolar plate that has been studied more in recent years. They use graphite as the main conductive filler, combined with thermosetting or thermoplastic resin binders and chemical additives, and are molded under heating and pressure conditions. It makes up for the shortcomings of pure graphite bipolar plates, which are brittle and have poor mechanical properties, but their conductivity is not as good as that of graphite bipolar plates; they are more corrosion-resistant than metal bipolar plates, but their air tightness is not as good as that of metal bipolar plates. Summary of the invention
[0004] Therefore, the technical problem to be solved by the present invention is to overcome the defect that the bipolar plate in the prior art is difficult to have high conductivity, corrosion resistance and sealing performance, thereby providing a bipolar plate and a preparation method thereof.
[0005] To this end, the present invention provides the following technical solutions:
[0006] A bipolar plate comprises the following raw materials in parts by weight:
[0007]
[0008] The composite polymer filler includes at least one of polyethylene, polyamide, polysiloxane, polyetheretherketone, polyimide, polyphenylene sulfide or polybenzimidazole.
[0009] Optionally, the distribution of the graphite particle size is as follows: 95% of the graphite particles have a particle size of less than 75 μm, 50% of the particles have a particle size of less than 25 μm, and 20% of the particles have a particle size of less than 15 μm; the specific surface area of the graphite particles is 300-600 m 2 / g.
[0010] Optionally, the carbon black particle size distribution is as follows: 95% of the carbon black particles have a particle size of less than 50 μm, 50% of the particles have a particle size of less than 15 μm, and 20% of the particles have a particle size of less than 5 μm; the carbon black particles have a specific surface area of 100-500 m 2 / g.
[0011] Optionally, the titanium carbide particle size distribution is as follows: 95% of the titanium carbide particles have a particle size of less than 150 μm, 50% of the particles have a particle size of less than 65 μm, and 20% of the particles have a particle size of less than 25 μm.
[0012] The present invention provides a method for preparing the bipolar plate, comprising the following steps:
[0013] Titanium carbide, graphite, carbon black and composite polymer filler are taken according to the formula to prepare a preform;
[0014] The obtained preform is heated and pressurized to form a bipolar plate.
[0015] Optionally, before the step of preparing the preform, the mixed powder of titanium carbide and graphite is added into the organic solution in advance, mixed and then dried; since the mixed powder of titanium carbide and graphite is easy to generate heat, wet mixing and drying is selected.
[0016] Optionally, the organic solution is a mixture of dimethyl sulfoxide and ethanol;
[0017] Optionally, the volume ratio of dimethyl sulfoxide to ethanol is 1:1.2-1:2.0;
[0018] Optionally, the mass ratio of the organic solution to the mixed powder is 4:1-8:1.
[0019] Optionally, in the step of preparing the preform, the raw materials are mixed by ball milling, and the ball milling conditions are: a ball-to-material ratio of 1:1, a rotation speed of 200-300 rpm, forward and reverse cycle intermittent ball milling, and the ball milling time is at least 420 minutes.
[0020] Optionally, the heating temperature is 160-220° C., and the heating time is 12-15 minutes.
[0021] Optionally, the heating step adopts a gradient temperature change program for heating, and the gradient temperature change program is as follows: after the room temperature is raised to 160°C-220°C, it is kept warm for 12-15 minutes, and then slowly cooled to 100°C-105°C at a cooling rate of ≤3K / min.
[0022] Optionally, the pressurization condition is 10 bar to 40 bar;
[0023] Optionally, a gradient pressure change program is used in the pressurization step, and the gradient pressure change program is as follows: the mold is opened for 7-17 seconds, the material is added for 20-30 seconds, the pressure rises from zero to 10 bar to 40 bar within 10-20 seconds of mold closing, the curing cycle is 73-120 seconds, and the mold is opened and taken out.
[0024] The technical solution of the present invention has the following advantages:
[0025] 1. A bipolar plate provided by the present invention comprises the following raw materials in parts by weight: 20-117 parts by weight of titanium carbide; 7-10 parts by weight of graphite; 0-3 parts by weight of carbon black; and 0-87 parts by weight of a composite polymer filler. The raw materials in the above specific proportions can be used to construct a three-dimensional conductive network through hot pressing to prepare a bipolar plate with good comprehensive performance, high electrical conductivity, and both corrosion resistance and sealing properties.
[0026] 2. The bipolar plate provided by the present invention has the following distribution of graphite particle size: 95% of the graphite particles have a particle size of less than 75 μm, 50% of the particles have a particle size of less than 25 μm, and 20% of the particles have a particle size of less than 15 μm; the specific surface area of the graphite particles is 300-600 m 2 / g; by selecting graphite with the above-mentioned particle size distribution and specific surface area, the size level can be matched with other raw materials, and the conductivity can be comprehensively improved through the morphology of each raw material, the connection mode between the raw materials that affect electron transport, and the structure of each raw material.
[0027] 3. A bipolar plate provided by the present invention, wherein the carbon black particle size distribution is as follows: 95% of the carbon black particles have a particle size of less than 50 μm, 50% of the particles have a particle size of less than 15 μm, and 20% of the particles have a particle size of less than 5 μm; the carbon black particles have a specific surface area of 100-500 m 2 / g; by selecting carbon black with the above-mentioned particle size distribution and specific surface area, the size level can be matched with other raw materials, and the conductivity can be comprehensively improved through the morphology of each raw material, the connection mode between the raw materials that affect electron transport, and the structure of each raw material.
[0028] 4. The present invention provides a bipolar plate, wherein the titanium carbide particle size distribution is as follows: 95% of the titanium carbide particles have a particle size of less than 150 μm, 50% of the particles have a particle size of less than 65 μm, and 20% of the particles have a particle size of less than 25 μm; by selecting titanium carbide with the above particle size distribution, the size level can be matched with other raw materials, and the conductivity can be comprehensively improved through the morphology of each raw material, the connection method between the raw materials that affects electron transmission, and the structure of each raw material.
[0029] 5. The present invention provides a method for preparing a bipolar plate, which has a simple process and can further improve the conductivity, corrosion resistance and sealing of the prepared bipolar plate by controlling the heating conditions and pressurization conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0031] Figure 1 These are the current density test results of the bipolar plate of the present invention and the commercially available Schmidt plate and composite plate in Experimental Example 2 of the present invention. DETAILED DESCRIPTION
[0032] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.
[0033] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.
[0034] Example 1
[0035] The formula of a bipolar plate provided in this embodiment is:
[0036]
[0037] The composite polymer filler includes 10 kg of polyethylene, 10 kg of polyamide, 10 kg of polysiloxane, 10 kg of polyetheretherketone, 10 kg of polyimide, 20 kg of polyphenylene sulfide and 17 kg of polybenzimidazole.
[0038] The distribution of the graphite particle size is as follows: 95% of the graphite particles have a particle size of less than 75 μm, 50% of the particles have a particle size of less than 25 μm, and 20% of the particles have a particle size of less than 15 μm; the specific surface area of the graphite particles is 600 m 2 / g.
[0039] The distribution of the carbon black particle size is as follows: 95% of the carbon black particles have a particle size of less than 50 μm, 50% of the particles have a particle size of less than 15 μm, and 20% of the particles have a particle size of less than 5 μm; the carbon black particles have a specific surface area of 500 m 2 / g.
[0040] The particle size distribution of titanium carbide is as follows: 95% of the particles of titanium carbide have a particle size of less than 150 μm, 50% of the particles have a particle size of less than 65 μm, and 20% of the particles have a particle size of less than 25 μm.
[0041] Preparation method:
[0042] (1) adding a mixed powder of graphite and titanium carbide particles to a mixed solution of dimethyl sulfoxide and ethanol, mixing well and then drying in a vacuum oven; the volume ratio of dimethyl sulfoxide to ethanol is 1:1.2; the mass ratio of the organic solution to the mixed powder is 8:1;
[0043] (2) preparing a preform of titanium carbide, graphite, and a composite filler, adding the mixed powder of titanium carbide, graphite, and the composite filler into a ball mill for ball milling and mixing, wherein the ball milling and mixing conditions are as follows: using a zirconium oxide ball mill and grinding beads, a ball-to-material ratio of 1:1, a rotation speed of 200 rpm, using a forward and reverse cycle intermittent ball mill, and the ball milling time is at least 420 minutes;
[0044] (3) The mixture is then pressed into a bipolar plate under heating and pressurizing conditions, and is heated using a gradient temperature program. The gradient temperature program is as follows: after the room temperature (25°C) is raised to 160°C, it is kept warm for 12 minutes, and then slowly cooled to 100°C at a cooling rate of 3K / min; the mixture under the above temperature conditions is then fed into a molding machine, specifically: the mold is opened for 7 seconds, the material is added for 20 seconds, the pressure is raised from zero to 35 bar within 10 seconds of the mold closing, the curing cycle is 73 seconds, and the mold is opened and taken out.
[0045] Example 2
[0046] The formula of a bipolar plate provided in this embodiment is:
[0047]
[0048] The composite polymer filler includes at least one of polyethylene, polyamide, polysiloxane, polyetheretherketone, polyimide, polyphenylene sulfide or polybenzimidazole.
[0049] The distribution of the graphite particle size is as follows: 95% of the graphite particles have a particle size of less than 75 μm, 50% of the particles have a particle size of less than 25 μm, and 20% of the particles have a particle size of less than 15 μm; the specific surface area of the graphite particles is 400 m 2 / g.
[0050] The distribution of the carbon black particle size is as follows: 95% of the carbon black particles have a particle size of less than 50 μm, 50% of the particles have a particle size of less than 15 μm, and 20% of the particles have a particle size of less than 5 μm; the specific surface area of the carbon black particles is 300 m 2 / g.
[0051] The particle size distribution of titanium carbide is as follows: 95% of the particles of titanium carbide have a particle size of less than 150 μm, 50% of the particles have a particle size of less than 65 μm, and 20% of the particles have a particle size of less than 25 μm.
[0052] Preparation method:
[0053] (1) adding a mixed powder of graphite and titanium carbide particles to a mixed solution of dimethyl sulfoxide and ethanol, mixing well and drying in a vacuum oven; the volume ratio of dimethyl sulfoxide to ethanol is 1:2.0; the mass ratio of the organic solution to the mixed powder is 4:1;
[0054] (2) preparing a preform of titanium carbide, graphite and carbon black, adding the mixed powder of titanium carbide, graphite and carbon black into a ball mill for ball milling and mixing, wherein the ball milling and mixing conditions are as follows: using a zirconium oxide ball mill and grinding beads, a ball-to-material ratio of 1:1, a rotation speed of 300 rpm, using a forward and reverse cycle intermittent ball mill, and the ball milling time is at least 430 minutes;
[0055] (3) The powder is placed in a mold and then pressed into a bipolar plate under heating and pressure conditions. The heating is performed using a gradient temperature program. The gradient temperature program is as follows: after the room temperature (25°C) is raised to 220°C, it is kept warm for 15 minutes, and then slowly cooled to 105°C at a cooling rate of ≤3K / min. The mixture under the above temperature conditions is then fed into a molding machine. Specifically, the mold is opened for 17 seconds, the material is added for 30 seconds, the pressure is raised from zero to 10 bar within 20 seconds of mold closing, the curing cycle is 120 seconds, and the mold is opened and taken out.
[0056] Example 3
[0057] The formula of a bipolar plate provided in this embodiment is:
[0058]
[0059] The composite polymer filler includes 8kg of polyethylene, 10kg of polyetheretherketone, 17kg of polyimide and 10kg of polyphenylene sulfide.
[0060] The distribution of the graphite particle size is as follows: 95% of the graphite particles have a particle size of less than 65 μm, 50% of the particles have a particle size of less than 15 μm, and 20% of the particles have a particle size of less than 5 μm; the specific surface area of the graphite particles is 300 m 2 / g.
[0061] The distribution of the carbon black particle size is as follows: 95% of the carbon black particles have a particle size of less than 45 μm, 50% of the particles have a particle size of less than 10 μm, and 20% of the particles have a particle size of less than 1 μm; the specific surface area of the carbon black particles is 100 m 2 / g.
[0062] The particle size distribution of titanium carbide is as follows: 95% of the particles of titanium carbide have a particle size of less than 120 μm, 50% of the particles have a particle size of less than 35 μm, and 20% of the particles have a particle size of less than 5 μm.
[0063] Preparation method:
[0064] (1) adding a mixed powder of graphite and titanium carbide particles to a mixed solution of dimethyl sulfoxide and ethanol, mixing well and then drying in a vacuum oven; the volume ratio of dimethyl sulfoxide to ethanol is 1:1.6; the mass ratio of the organic solution to the mixed powder is 6:1;
[0065] (2) preparing a preform of titanium carbide, graphite, carbon black, and a composite filler, adding a mixed powder of titanium carbide, graphite, carbon black, and a composite filler into a ball mill for ball milling and mixing, wherein the ball milling and mixing conditions are as follows: using a zirconium oxide ball mill and grinding beads, a ball-to-material ratio of 1:1, a rotation speed of 250 rpm, using a forward and reverse cycle intermittent ball mill, and a ball milling time of 450 minutes;
[0066] (3) The mixture is then pressed into bipolar plates under heating and pressure conditions, and heated using a gradient temperature program. The gradient temperature program is as follows: after the room temperature (25°C) is raised to 190°C, it is kept warm for 14 minutes, and then slowly cooled to 103°C at a cooling rate of 2K / min. The mixture under the above temperature conditions is then fed into a molding machine. Specifically, the mold is opened for 12 seconds, the material is added for 25 seconds, the pressure is raised from zero to 35 bar within 15 seconds of mold closing, the curing cycle is 85 seconds, and the mold is opened and taken out.
[0067] Comparative Example 1
[0068] The formula of a bipolar plate provided in this embodiment is:
[0069]
[0070] The composite polymer filler includes 8kg of polyethylene, 10kg of polyetheretherketone, 17kg of polyimide and 10kg of polyphenylene sulfide.
[0071] In the above formula, the graphite particle size is less than 75 μm, the carbon black particle size is less than 50 μm, and the titanium carbide particle size is less than 150 μm.
[0072] Preparation method:
[0073] (1) adding a mixed powder of graphite and titanium carbide particles to a proper amount of ethanol in dimethyl sulfoxide, mixing well and drying in a vacuum oven; the volume ratio of dimethyl sulfoxide to ethanol is 1:1.6; the mass ratio of the organic solution to the mixed powder is 6:1;
[0074] (2) preparing a preform of titanium carbide, graphite, carbon black, and composite filler, adding the mixed powder into a ball mill for ball milling, wherein the ball milling mixing conditions are as follows: using a zirconia ball mill and grinding beads, a ball-to-material ratio of 1:1, a rotation speed of 200 rpm, using forward and reverse cycle intermittent ball milling, and the ball milling time is at least 420 minutes;
[0075] (3) The mixture is then pressed into bipolar plates under heating and pressure conditions, and heated using a gradient temperature program. The gradient temperature program is as follows: after the room temperature (25°C) is raised to 190°C, it is kept warm for 14 minutes, and then slowly cooled to 103°C at a cooling rate of 2K / min. The mixture under the above temperature conditions is then fed into a molding machine. Specifically, the mold is opened for 12 seconds, the material is added for 25 seconds, the pressure is raised from zero to 35 bar within 15 seconds of mold closing, the curing cycle is 85 seconds, and the mold is opened and taken out.
[0076] Test Example 1
[0077] 1. Conductivity
[0078] Conductivity is measured according to ASTM C611-98 standard.
[0079] The bipolar plates of Examples 1-3 and the bipolar plate of Comparative Example 1 were subjected to conductivity measurement.
[0080] The results are shown in Table 1:
[0081] Table 1. Conductivity
[0082]
[0083]
[0084] It can be concluded from the above that the bipolar plate prepared by the present invention has very good electrical conductivity, and the electrical conductivity can reach 75.2S / cm.
[0085] 2. Anti-corrosion
[0086] The corrosion resistance was determined according to the cyclic voltammetry method.
[0087] The anti-corrosion performance of the bipolar plates of Examples 1-3 and the bipolar plates of the comparative example was measured.
[0088] The results are shown in Table 2:
[0089] Table 2. Corrosion resistance
[0090] <![CDATA[Corrosion impedance (μA·cm -2 )]]> Example 1 0.85 Example 2 0.62 Example 3 0.52 Comparative Example 1 1.04
[0091] From the above, it can be seen that the bipolar plate prepared by the present invention has strong corrosion resistance, and the lowest corrosion resistance can reach 0.52μA·cm -2 .
[0092] 3. Airtightness
[0093] The air tightness test is carried out according to ASTM D1434 standard.
[0094] The bipolar plates of Examples 1-3 and the bipolar plates of the comparative example were tested for air tightness. The test results were
[0095] As shown in Table 3:
[0096] Table 3. Air tightness
[0097] Example 1 <![CDATA[<1.1×10 -14 ]]> Example 2 <![CDATA[<1.3×10 -14 ]]> Example 3 <![CDATA[<0.9×10 -14 ]]> Comparative Example 1 <![CDATA[<1.3×10 -14 ]]>
[0098] From the above, it can be seen that the bipolar plate prepared by the present invention has good air tightness, the lowest of which can reach <0.9×10 -14 .
[0099] Test Example 2
[0100] The bipolar plate of Example 1, commercial graphite plate (purchased from Ballard) and commercial composite plate (purchased from Schunk) were used to measure the current density according to ASTM C611-98. The results are as follows: Figure 1 As shown in the figure, it can be seen that the current density of Example 1 increases gently with the electric potential, showing strong corrosion resistance. At the same time, the current density is significantly better than that of commercial graphite plates and commercial composite plates, indicating that the conductivity of the bipolar plate of the invention is greatly improved compared with commercial graphite plates and commercial composite plates.
[0101] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.
Claims
1. A bipolar plate, characterized in that: It is composed of the following raw materials in parts by weight: The composite polymer filler includes at least one of polyethylene, polyamide, polysiloxane, polyetheretherketone, polyimide, polyphenylene sulfide or polybenzimidazole; The distribution of the graphite particle size is as follows: 95% of the graphite particles have a particle size of less than 75 μm, 50% of the particles have a particle size of less than 25 μm, and 20% of the particles have a particle size of less than 15 μm; the specific surface area of the graphite particles is 300-600 m 2 / g; The distribution of the carbon black particle size is as follows: 95% of the carbon black particles have a particle size of less than 50 μm, 50% of the particles have a particle size of less than 15 μm, and 20% of the particles have a particle size of less than 5 μm; the specific surface area of the carbon black particles is 100-500 m 2 / g; The particle size distribution of the titanium carbide is as follows: 95% of the particles in the titanium carbide particles have a particle size of less than 150 μm, 50% of the particles have a particle size of less than 65 μm, and 20% of the particles have a particle size of less than 25 μm.
2. A method for preparing a bipolar plate according to claim 1, characterized in that: The steps include: Titanium carbide, graphite, carbon black and composite polymer filler are taken according to the formula to prepare a preform; The obtained preform is heated and pressurized to form a bipolar plate.
3. The method for preparing a bipolar plate according to claim 2, characterized in that: Before the step of preparing the preform, the method also includes adding the mixed powder of titanium carbide and graphite into the organic solution, mixing them evenly and then drying them.
4. The method for preparing a bipolar plate according to claim 3, characterized in that: The organic solution is a mixture of dimethyl sulfoxide and ethanol.
5. The method for preparing a bipolar plate according to claim 4, characterized in that: The volume ratio of dimethyl sulfoxide to ethanol is 1:1.2-1:2.0; and / or The mass ratio of the organic solution to the mixed powder is 4:1-8:
1.
6. The method for preparing a bipolar plate according to claim 2 or 3, characterized in that: In the step of preparing the preform, the raw materials are ball-milled and mixed, and the ball-milling conditions are: the ball-to-material ratio is 1:1, the rotation speed is 200-300 rpm, forward and reverse cycle intermittent ball milling is adopted, and the ball milling time is at least 420 minutes.
7. The method for preparing a bipolar plate according to claim 2 or 3, characterized in that: The heating temperature is 160-220° C., and the heating time is 12-15 minutes.
8. The method for preparing a bipolar plate according to claim 2 or 3, characterized in that: The heating step adopts a gradient temperature program for heating, and the gradient temperature program is as follows: after the room temperature is raised to 160°C-220°C, it is kept warm for 12-15 minutes, and then slowly cooled to 100°C-105°C at a cooling rate of ≤3K / min.
9. The method for preparing a bipolar plate according to claim 2 or 3, characterized in that: The pressurization condition is 10 bar to 40 bar.
10. The method for preparing a bipolar plate according to claim 9, characterized in that: The pressurization step adopts a gradient pressure change program, and the gradient pressure change program is as follows: the mold is opened for 7-17 seconds, the material is added for 20-30 seconds, the pressure rises from zero to 10 bar to 40 bar within 10-20 seconds of mold closing, the curing cycle is 73-120 seconds, and the mold is opened and taken out.
Citation Information
Patent Citations
Preparation method of composite graphite bipolar plate
CN112290040A